A Deeply Branching Thermophilic Bacterium with an Ancient Acetyl-CoA Pathway Dominates a Subsurface Ecosystem - Takami, Hideto; Noguchi, Hideki; Takaki, Yoshihiro; Uchiyama, Ikuo; Toyoda, Atsushi; Nishi, Shinro; Chee, Gab-Joo; Arai, Wataru; Nunoura, Takuro; Itoh, Takehiko; Hattori, Masahira; Takai, Ken (PLOS ONE, 2012)
A nearly complete genome sequence of Candidatus ‘Acetothermum autotrophicum’, a presently uncultivated bacterium in candidate division OP1, was revealed by metagenomic analysis of a subsurface thermophilic microbial mat community. Phylogenetic analysis based on the concatenated sequences of proteins common among 367 prokaryotes suggests that Ca. ‘A. autotrophicum’ is one of the earliest diverging bacterial lineages. It possesses a folate-dependent Wood-Ljungdahl (acetyl-CoA) pathway of CO2 fixation, is predicted to have an acetogenic lifestyle, and possesses the newly discovered archaeal-autotrophic type of bifunctional fructose 1,6-bisphosphate aldolase/phosphatase. A phylogenetic analysis of the core gene cluster of the acethyl-CoA pathway, shared by acetogens, methanogens, some sulfur- and iron-reducers and dechlorinators, supports the hypothesis that the core gene cluster of Ca. ‘A. autotrophicum’ is a particularly ancient bacterial pathway. The habitat, physiology and phylogenetic position of Ca. ‘A. autotrophicum’ support the view that the first bacterial and archaeal lineages were H2-dependent acetogens and methanogenes living in hydrothermal environments.